Pengaruh Model Pembelajaran Kooperatif Tipe Kancing Gemerincing dan Motivasi Belajar terhadap Hasil Belajar Mahasiswa pada Mata Kuliah Ekonomi Politik di Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Batanghari Jambi - Diliza Afrila (Universitas Batanghari Jambi, 2021)
This study aims to determine (1) Student learning outcomes in the Political Economy course taught using cooperative learning model type Kancing Gemerincing are higher than students taught using conventional learning models in the Economic Education Study Program, (2) Student learning outcomes in the Political Economy course who has high learning motivation which is taught by using the cooperative learning model type Kancing Gemerincing is higher than students who have high learning motivation who are taught using conventional learning models in the Economic Education Study Program, (3) Student learning outcomes in the Political Economy courses who have low learning motivation who are taught using the cooperative learning model type Kancing Gemerincing are higher than students who have low learning motivation who are taught using conventional learning models in the Education Study Program Economics, and (4) the interaction between cooperative learning model type Kancing Gemerincing and learning motivation towards student learning outcomes in the Political Economy course in the Economic Education Study Program. This type of research is a quasi experiment. The study population was 27 students of the Economic Education Study Program Semester VI / A1 and VI / A2 Academic Year 2019/2020. The sampling technique was purposive sampling (purposive sampling). The results showed that (1) Student learning outcomes in the Political Economy course taught by using the cooperative learning model type Kancing Gemerincing were higher than those taught using conventional learning models. This is indicated by the t value of 2.159 and the probability value of 0.041. So that the probability value of 0.041 < 0.05 then H0 is rejected, (2) Student learning outcomes in the Political Economy course who have high learning motivation who are taught using the cooperative learning model type Kancing Gemerincing are higher than students who have high learning motivation being taught with conventional learning models. This is indicated by the t value of 7.260 and the probability value of 0.001. Thus, the probability value of 0.001 < 0.05 then H0 is rejected, (3) The learning outcomes of students in the Political Economy course who have low learning motivation who are taught using cooperative learning model type Kancing Gemerincing are higher than students who have low learning motivation which taught by conventional learning models. This is indicated by the t value of 1.532 and the probability value of 0.006. Thus, the probability value of 0.006 < 0.05 then H0 is rejected, and (4) There is no interaction between the cooperative learning model type Kancing Gemerincing and learning motivation on student learning outcomes in the Political Economy course. This is indicated by the Sig level of 0.205. This means that the value of Sig is greater than the value of α = 0.05 (sig α), so the null hypothesis (Ho) is accepted.